Battery monomer, battery device and power utilization device
By adding porous carbon materials to the positive electrode material of lithium-ion batteries and controlling the carbon content, the problem of low instantaneous discharge power of lithium-ion batteries at low temperatures is solved, and a high-performance battery under low temperature conditions is achieved.
Patent Information
- Application Number
- CN202411770662.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-15
AI Technical Summary
Lithium-ion batteries exhibit low instantaneous discharge power and storage life in low temperature environments, making it difficult to meet the demand for high-performance batteries in the new energy industry.
By introducing porous carbon material into the positive electrode material of the battery cell and controlling its carbon content between 3% and 10%, the instantaneous discharge power of the battery cell at low temperatures is enhanced while maintaining energy density and storage life.
The instantaneous discharge power of the battery cell under low temperature conditions is achieved, while avoiding the negative impact on energy density and storage life.
Smart Images

Figure CN119833715A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a battery cell, a battery device and an electrical device. Background Art
[0002] With the development of the new energy industry, lithium-ion batteries are widely used in electric vehicles, drones, aerospace, medical equipment and other fields due to their high capacity and light weight. With the continuous expansion of the application fields of lithium-ion batteries and the needs of social development, lithium-ion batteries are easily affected by low temperatures, resulting in a significant decline in their performance. Therefore, people have put forward higher requirements for the performance of lithium-ion batteries in low-temperature scenarios, such as the instantaneous discharge power and storage life of battery cells at low temperatures. Summary of the invention
[0003] In view of the above problems, the present application provides a battery cell, a battery device and an electrical device thereof, which can improve the instantaneous discharge power of the battery cell at low temperature while taking into account the energy density and storage life of the battery cell.
[0004] In the first aspect, the present application provides a battery cell, comprising a positive electrode plate, a negative electrode plate and an isolation membrane located between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode film layer comprises a positive electrode material, and the positive electrode material comprises a carbon material and a porous carbon material on at least a portion of the surface of a lithium iron phosphate material; based on the total mass of the positive electrode material, the carbon content of the positive electrode material is 3% to 10%.
[0005] In the embodiment of the present application, adding porous carbon material to the positive electrode material is beneficial to improving the discharge power of the battery cell at low temperature. On the one hand, the porous carbon material has the characteristics of porosity and large specific surface area, and lithium ions can be quickly deintercalated at the active sites on the surface of the porous carbon material, which is beneficial to improving the instantaneous discharge power of the battery cell at low temperature. However, if the content of porous carbon material added is too high, the energy density of the battery cell will be low. By controlling the carbon content of the positive electrode material to 3% to 10%, the mass content of the porous carbon material added to the positive electrode material can be further controlled within a suitable range. Therefore, by controlling the carbon content of the positive electrode material within the above range, the instantaneous power of the battery cell at low temperature can be improved and the impact on the energy density of the battery cell can be reduced without affecting the storage life.
[0006] In some embodiments, the positive electrode film layer includes a first film layer and a second film layer, wherein the first film layer is disposed on at least one surface of the positive electrode current collector, and the first film layer includes a lithium iron phosphate material; the second film layer is disposed on the surface of the first film layer away from the positive electrode current collector, and the second film layer includes a porous carbon material. The arrangement of the first film layer and the second film layer is conducive to improving the instantaneous discharge power of the battery cell at low temperature.
[0007] In some embodiments, the thickness of the first film layer is 50 μm to 100 μm; and / or the thickness of the second film layer is 4 μm to 14 μm. Controlling the thickness of the first film layer and the second film layer within the above range is conducive to improving the instantaneous discharge power of the battery cell at low temperature while taking into account the energy density.
[0008] In some embodiments, based on the total mass of the positive electrode material, the carbon content of the first film layer is 1.5% to 3%; and / or the carbon content of the second film layer is 2% to 7%. Controlling the carbon content of the first film layer and the second film layer within the above range is conducive to improving the instantaneous discharge power of the battery cell at low temperature while taking into account the energy density.
[0009] In some embodiments, the mass content of the porous carbon material in the positive electrode material is 2% to 7% based on the mass of the positive electrode material. Controlling the mass content of the porous carbon material within the above range is conducive to improving the instantaneous discharge power of the battery cell at low temperature while taking into account the energy density of the battery cell.
[0010] In some embodiments, the porous carbon material includes at least one of activated carbon, carbon molecular sieve, activated carbon fiber and mesoporous carbon. The porous carbon material has a large specific surface area and is porous. During the charge and discharge process of the battery cell, lithium ions can be quickly deintercalated on the surface of the material, which is beneficial to improve the instantaneous discharge power of the battery cell at low temperature.
[0011] In some embodiments, the volume average particle size Dv50 of the porous carbon material is 0.50 μm to 10 μm. Controlling the pore size of the porous carbon material within the above range is beneficial to improving the instantaneous discharge power of the battery cell at low temperature.
[0012] In some embodiments, the specific surface area of the porous carbon material is 1000 m 2 / g to 2000m 2 Controlling the specific surface area of the porous carbon material within the above range is beneficial to the instantaneous discharge power of the battery cell at low temperature.
[0013] In some embodiments, the porous carbon material is used as a positive electrode material after being heat-treated at 900°C to 1100°C, so that the oxygen-containing groups on the surface of the porous carbon material are reduced. By controlling the temperature of the heat treatment of the porous carbon material within the above range, the oxygen-containing functional groups in the porous carbon material can be removed, thereby further improving the discharge power of the battery cell at low temperature.
[0014] In some embodiments, the carbon content of the lithium iron phosphate material is 1% to 2% based on the total mass of the lithium iron phosphate material. Controlling the carbon content of the lithium iron phosphate material within the above range is conducive to improving the conductivity of the lithium iron phosphate material, thereby improving the discharge power of the battery cell at low temperature.
[0015] In some embodiments, the lithium iron phosphate material includes lithium iron phosphate and modified compounds thereof, which is beneficial to the safety performance and storage life of the battery cell.
[0016] In some embodiments, the positive electrode material includes a conductive agent, which may be at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Using the above materials as conductive agents can improve the conductivity of the positive electrode material, reduce internal resistance, and help improve the instantaneous discharge power of the battery cell at low temperatures.
[0017] In some embodiments, based on the total mass of the positive electrode material, the carbon content of the conductive agent is 0.2% to 1%. Controlling the carbon content of the conductive agent in the positive electrode material within the above range is beneficial to the discharge power of the battery cell.
[0018] In some embodiments, the gram capacity of the positive electrode material is 130 mAh / g to 170 mAh / g. When the gram capacity of the positive electrode sheet is controlled within the above range, the energy density of the battery cell is relatively high.
[0019] In some embodiments, the compaction density of the positive electrode film layer of the battery cell at 100% charge state is 2.00 g / cm 3 Up to 2.50g / cm 3 Controlling the compaction density of the positive electrode film layer within the above range is beneficial to the transmission of lithium ions and can further improve the instantaneous discharge power of the battery cell at low temperatures.
[0020] In a second aspect, the present application provides a battery device, which includes a plurality of battery cells according to any embodiment of the present application.
[0021] In a third aspect, the present application proposes an electrical device, which includes a battery device according to any embodiment of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0023] Figure 1 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0024] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0025] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0026] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0027] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0028] Figure 6 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.
[0029] In the drawings, the drawings are not drawn to scale.
[0030] Marking Description:
[0031] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0032] The following detailed description and drawings of the embodiments of the present application are used to illustrate the principles of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.
[0033] In the description of the present application, it should be noted that, unless otherwise specified, "multiple" means more than two; the terms "upper", "lower", "left", "right", "inside", "outside", etc., indicating the orientation or positional relationship, are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. "Vertical" is not strictly vertical, but is within the allowable error range. "Parallel" is not strictly parallel, but is within the allowable error range.
[0034] The directional words appearing in the following description are all directions shown in the figures, and do not limit the specific structure of this application. In the description of this application, it should also be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances.
[0035] With the rapid development of the new energy industry, the application field of lithium-ion batteries continues to expand, and people's performance requirements for lithium-ion batteries are getting higher and higher. When lithium-ion batteries are started in a low-temperature environment, the impedance of lithium-ion batteries increases, and the instantaneous discharge power is poor, resulting in slow startup of electrical devices using lithium-ion batteries. The conventional solution is to improve the electrolyte of the battery cell, introduce high-conductivity electrolyte, improve ion conductivity, and thus improve the instantaneous discharge power of the battery cell. However, the introduction of high-conductivity electrolyte into the battery cell will increase the side reactions, which will reduce the storage life of the battery cell.
[0036] In order to solve the above problems, the embodiments of the present application reasonably design the positive electrode material of the battery cell to improve the instantaneous power of the battery cell at low temperature while taking into account the storage life.
[0037] In the first aspect, the embodiment of the present application proposes a battery cell. The battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, the positive electrode film layer includes a positive electrode material, and the positive electrode material includes a carbon material and a porous carbon material on at least a portion of the surface of a lithium iron phosphate material; based on the total mass of the positive electrode material, the carbon content of the positive electrode material is 3% to 10%.
[0038] Porous carbon materials refer to carbonaceous materials with rich pore systems, which can be selected as carbonaceous materials with different pore sizes. These pore structures make porous carbon materials have highly developed specific surface area and pore structure, thus giving them unique physical and chemical properties.
[0039] “At least a portion of the surface” may refer to a portion of the surface of an object or the entire surface of an object.
[0040] “Carbon material” refers to a substance that can improve the conductivity of lithium iron phosphate materials, and can be amorphous carbon, carbon black or graphite.
[0041] In some embodiments, the carbon content of the positive electrode material may be derived from the carbon material on at least part of the surface of lithium iron phosphate, and / or, the carbon content of the positive electrode material may be derived from the porous carbon material; the carbon content of the positive electrode material may also be derived from the binder and the conductive agent.
[0042] In some embodiments, the electrode sheet includes a binder, and after the electrode sheet is cleaned and calcined, if some organic components are converted into carbon-containing materials and remain in the positive electrode material, they are also included in the calculation range of the carbon content.
[0043] In some embodiments, based on the carbon content of the positive electrode material, the carbon content of the carbon material, binder and conductive agent on at least part of the surface of the lithium iron phosphate material is relatively small and relatively fixed. Therefore, the change of the carbon content in the positive electrode material from 3% to 10% comes from the amount of added porous carbon material mass content. Therefore, in the embodiments of the present application, the carbon content of the positive electrode material can be regulated by regulating the mass content of the porous carbon material in the positive electrode material.
[0044] In the embodiments of the present application, the carbon content of the positive electrode material can be detected by equipment and methods known in the art, according to the high-frequency induction furnace combustion thick infrared absorption method, for example, the battery cell is discharged to 2V at 0.33C and then the positive electrode sheet is disassembled, cleaned and dried with DMC, and the positive electrode material obtained after high-temperature calcination and impurity removal is ground into powder as a sample, and the CS-800 carbon-sulfur analyzer of Germany's Elte Company is used for detection in accordance with GB / T 20123-2006.
[0045] In some embodiments, the carbon content of the positive electrode material is controlled to be 3% to 10%. For example, the carbon content of the positive electrode material can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any two of the above values.
[0046] By introducing porous carbon materials into the positive electrode materials, on the one hand, during the charge and discharge process of the battery cell, lithium ions can be quickly deintercalated and deintercalated at the surface active sites of the porous carbon materials, thereby significantly reducing the solid phase impedance of the positive electrode in the process and further improving the instantaneous discharge power of the battery cell at low temperatures; on the other hand, by introducing porous carbon materials into the positive electrode materials, the storage life of the battery cell will not be affected.
[0047] However, too high a carbon content in the positive electrode material means that the amount of positive electrode material providing active lithium is reduced, which will reduce the energy density of the battery cell; too low a carbon content in the positive electrode material means that the mass content of the added porous carbon material is too low, which will result in no obvious improvement in the instantaneous discharge power performance of the battery cell; therefore, controlling the carbon content of the positive electrode material to 3% to 10% can further control the mass content of the porous carbon material in the positive electrode material within a suitable range, which is beneficial to improving the instantaneous discharge power of the battery cell at low temperatures and reducing the impact on the energy density of the battery cell.
[0048] The present application improves the instantaneous discharge power of the battery cell at low temperature while taking into account the energy density of the battery cell without affecting the storage life of the battery cell by reasonably designing the positive electrode material of the battery cell.
[0049] In the embodiment of the present application, the 100% state of charge and 0% state of charge of the battery cell are defined as follows: the battery cell is charged at a constant current charging rate of 0.33C to an upper limit charging voltage of 3.8V, and then charged at a constant voltage to 0.05C, corresponding to a 100% charged state of the battery cell; the battery cell is discharged at a constant current discharge rate of 0.33C to a cut-off voltage of 2V, corresponding to a 0% charged state of the battery cell.
[0050] In some embodiments, the positive electrode film layer includes a first film layer and a second film layer, the first film layer is arranged on at least one surface of the positive electrode current collector, and the first film layer includes a lithium iron phosphate material; the second film layer is arranged on the surface of the first film layer away from the positive electrode current collector, and the second film layer includes a porous carbon material.
[0051] Disposing the second film layer on at least the surface of the first film layer is conducive to the second film layer being infiltrated by the electrolyte, which can shorten the transmission distance of lithium ions on the surface of the porous carbon material between the positive and negative electrodes, and further improve the instantaneous discharge power of the battery cell at low temperature.
[0052] In some embodiments, the thickness of the first film layer is 50 μm to 100 μm; and / or, the thickness of the second film layer is 4 μm to 14 μm. For example, the thickness of the first film layer can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, or a range consisting of any two of the above values; the thickness of the second film layer can be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or a range consisting of any two of the above values.
[0053] In an embodiment of the present application, the thickness of the first film layer and the second film layer can be measured by plasma cutting the positive electrode plate along its thickness direction to obtain a cross-section of the positive electrode plate, and observing the cross-section through a scanning electron microscope (SEM). There are obvious dividing lines between different film layers, and the thickness of the first film layer and the second film layer can be obtained.
[0054] If the thickness of the first film layer is too thick, it will be detrimental to the electrolyte infiltration, thus affecting the performance of the battery cell. If the thickness of the first film layer is too thin, it will be detrimental to the energy density of the battery cell. Controlling the thickness of the first film layer within the above range will help improve the instantaneous discharge power of the battery cell at low temperature while taking into account the energy density.
[0055] If the thickness of the second film layer is too thick, it will be detrimental to the energy density of the battery cell. If the thickness of the second film layer is too thin, the improvement of the instantaneous discharge power performance of the battery cell at low temperature will not be obvious. Controlling the thickness of the second film layer within the above range will help improve the instantaneous discharge power of the battery cell at low temperature while taking into account the energy density.
[0056] In the embodiment of the present application, controlling the thickness of the first film layer and the second film layer within the above range is beneficial to improving the instantaneous discharge power of the battery cell at low temperature while reducing the impact on the energy density of the battery cell.
[0057] In some embodiments, based on the total mass of the positive electrode material, the carbon content of the first film layer is 1.5% to 3%; and / or, the carbon content of the second film layer is 2% to 7%. For example, the carbon content of the first film layer can be 1.5%, 1.8%, 2.1%, 2.4%, 2.7%, 3% or a range consisting of any two of the above values; the carbon content of the second film layer can be 2%, 3%, 4%, 5%, 6%, 7% or a range consisting of any two of the above values.
[0058] The carbon content of the first film layer comes from the binder, the conductive agent and the carbon material located on at least part of the surface of the lithium iron phosphate material, wherein the carbon content of the binder and the conductive agent is relatively fixed and relatively small, therefore, the change in the carbon content of the first film layer mainly comes from the carbon material located on at least part of the surface of the lithium iron phosphate material. The change in the carbon content of the first film layer can be controlled by regulating the content of the carbon material on at least part of the surface of the lithium iron phosphate material.
[0059] The carbon content of the second film layer comes from the binder, the conductive agent and the porous carbon material. Among them, the carbon content of the binder and the conductive agent is relatively fixed and small. Therefore, the change in the carbon content of the second film layer mainly comes from the porous carbon material. The change in the carbon content of the second film layer can be controlled by adjusting the mass content of the added porous carbon material.
[0060] In the embodiment of the present application, controlling the carbon content of the first film layer and the second positive electrode film layer within the above range is beneficial to improving the instantaneous discharge power of the battery cell at low temperature while reducing the impact on the energy density of the battery cell.
[0061] In some embodiments, based on the mass of the positive electrode material, the mass content of the porous carbon material in the positive electrode material is 2.0% to 7.0%. For example, the mass content of the porous carbon material can be 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0% or a range consisting of any two of the above values.
[0062] If the porous carbon material content in the positive electrode material is too low, the improvement in the instantaneous discharge power of the battery cell will not be obvious; if the porous carbon material content in the positive electrode material is too high, the energy density of the battery cell will be greatly reduced; therefore, controlling the porous carbon content in the positive electrode material within the above range can help improve the instantaneous power of the battery cell at low temperatures and reduce the impact on the energy density of the battery cell.
[0063] In some embodiments, the porous carbon material may be at least one of activated carbon, carbon molecular sieve, activated carbon fiber, and mesoporous carbon.
[0064] The above-mentioned porous carbon material has a large specific surface area and is also porous. During the charging and discharging process of the battery cell, the lithium ions on the surface of the porous carbon material can be quickly deintercalated, thereby increasing the migration rate of lithium ions in this process and further improving the instantaneous discharge power of the battery cell at low temperatures. On the other hand, the above-mentioned porous carbon material can improve the conductivity of the positive electrode material, which is beneficial to improving the discharge power of the battery cell at low temperatures.
[0065] In some embodiments, the volume average particle size Dv50 of the porous carbon material is 0.50 μm to 10 μm.
[0066] In the embodiments of the present application, the volume average particle size Dv50 refers to the particle size corresponding to 50% in the volume distribution, which can be detected by using equipment and methods known in the art. With reference to the test standard GB / T 19077-2016, the Dv50 of the particles is tested by a Mastersizer 2000E laser particle size analyzer.
[0067] In some embodiments, the volume average particle size Dv50 of the porous carbon material is controlled to be 0.50 μm to 10 μm. For example, the volume average particle size Dv50 of the porous carbon material can be 0.50 μm, 1.50 μm, 2.50 μm, 3.50 μm, 4.50 μm, 5.50 μm, 6.50 μm, 7.50 μm, 8.50 μm, 9.50 μm, 10 μm or a range consisting of any two of the above values.
[0068] If the volume average particle size Dv50 of the porous carbon material is too small, the porous carbon material will easily agglomerate in the slurry and will be difficult to disperse well; if the volume average particle size Dv50 of the porous carbon material is too large, the specific surface area utilization of the porous carbon material will become low, thereby affecting the instantaneous discharge power of the battery cell at low temperature; therefore, controlling the Dv50 of the porous carbon material within the above range is beneficial to improving the instantaneous discharge power of the battery cell at low temperature.
[0069] In some embodiments, the specific surface area of the porous carbon material is 1000 m 2 / g to 2000m 2 / g.
[0070] In the embodiments of the present application, the specific surface area of the porous carbon material can be detected by using equipment and methods known in the art. For example, the porous carbon material is used as a sample and tested according to the static nitrogen adsorption method, referring to the test standard GB / T 19587-2004, and a Tristarll 3020 specific surface area tester is selected for testing.
[0071] In some embodiments, the specific surface area of the porous carbon material is controlled to be 1000 m2 / g to 2000m 2 / g, for example, the specific surface area of the porous carbon material can be 1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g or a range consisting of any two of the above values.
[0072] Controlling the specific surface area of the porous carbon material within the above range, on the one hand, is conducive to the rapid deintercalation of lithium ions on the surface of the porous carbon material during the charge and discharge process of the battery cell, thereby increasing the migration rate of lithium ions in the process, thereby facilitating the improvement of the instantaneous discharge power of the battery cell at low temperatures; on the other hand, the porous carbon material has a larger specific surface area and the contact area with the electrolyte is also increased, which is conducive to the transmission of lithium ions at the phase interface and can improve the discharge power of the battery cell at low temperatures.
[0073] In some embodiments, the positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode collector, drying and cold pressing. The positive electrode film layer also includes a positive electrode binder and a positive electrode conductor. The embodiments of the present application have no particular restrictions on the types of positive electrode binders and positive electrode conductors. As an example, the positive electrode binder may include polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyacrylic acid and fluorine-containing acrylic resin. At least one of the resins. In some embodiments, based on the total mass of the positive electrode film layer, the mass content of the positive electrode binder is ≤5%; the positive electrode conductor includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0074] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, at least one foil of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy may be used. The composite current collector may include a polymer material base and a metal material layer formed on at least one surface of the polymer material base. As an example, the metal material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0075] In some embodiments, the porous carbon material is used as a positive electrode material after heat treatment, and the heat treatment temperature is 900°C to 1100°C, so that the oxygen-containing groups on the surface of the porous carbon material are reduced. For example, the heat treatment temperature can be 900°C, 925°C, 950°C, 975°C, 1000°C, 1025°C, 1050°C, 1075°C, 1100°C, or a range consisting of any two of the above values.
[0076] Porous carbon materials contain oxygen-containing functional groups, such as carboxyl and carbonyl groups, which will affect the ability of porous carbon materials to store lithium on their surface. Controlling the heat treatment temperature of porous carbon materials within the above range can effectively remove oxygen-containing functional groups in porous carbon materials, which is beneficial to the deintercalation of lithium ions on the surface of porous carbon materials, thereby further improving the instantaneous discharge power of battery cells.
[0077] In some embodiments, the carbon content of the lithium iron phosphate material is 1% to 2% based on the mass of the lithium iron phosphate material.
[0078] In the embodiment of the present application, the test of the carbon content in the lithium iron phosphate material refers to the test method of the carbon content in the positive electrode material mentioned above.
[0079] The carbon content of the lithium iron phosphate material comes from the carbon material on at least part of the surface of the lithium iron phosphate material. Controlling the carbon content of the lithium iron phosphate material can control the mass content of the carbon material. Controlling the carbon content of the lithium iron phosphate material within the above range can make the mass content of the carbon material within a suitable range, thereby improving the conductivity of the lithium iron phosphate material, thereby improving the discharge power of the battery cell at low temperature.
[0080] In some embodiments, the lithium iron phosphate material includes at least one of lithium iron phosphate and modified compounds thereof.
[0081] Modified compounds refer to substances obtained on the basis of lithium iron phosphate through modification methods such as doping or coating, such as composite materials of lithium iron phosphate and carbon.
[0082] The positive electrode material includes the compound within the above range, which is beneficial to improving the safety performance and storage life of the battery monomer.
[0083] In some embodiments, the positive electrode material includes a conductive agent, and the conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Using the above materials as conductive agents can improve the conductivity of the positive electrode material, reduce internal resistance, and help improve the instantaneous power of the battery cell at low temperatures.
[0084] In some embodiments, the carbon content of the conductive agent is 0.2% to 1% based on the total mass of the positive electrode material. For example, the carbon content of the conductive agent can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or a range consisting of any two of the above values. Controlling the carbon content of the conductive agent within the above range is conducive to improving the discharge power of the battery cell.
[0085] In some embodiments, the gram capacity of the positive electrode material is 130 mAh / g to 170 mAh / g.
[0086] In some embodiments, the gram capacity of the positive electrode material is controlled to be 130 mAh / g to 170 mAh / g. For example, the gram capacity of the positive electrode material can be 130 mAh / g, 140 mAh / g, 150 mAh / g, 160 mAh / g, 170 mAh / g, or a range consisting of any two of the above values.
[0087] In the embodiments of the present application, the gram capacity of the positive electrode material has a meaning well known in the art and can be tested using equipment and methods well known in the art. The test method for the first coulombic efficiency and the first discharge specific capacity in Appendix G of the national standard GB / T 24533-2019 can be used. Metal lithium is used as the negative electrode and a sample electrode comprising the above material is used as the positive electrode to assemble a half-button battery. Under the conditions of 23°C±2°C, the half-button battery is charged and discharged at a rate of 0.1C on a battery tester or other test equipment with equivalent performance to obtain the charge capacity, and then the capacity is divided by the mass of the electrode material to obtain the charge gram capacity parameter.
[0088] By controlling the gram capacity of the positive electrode sheet within the above range, the energy density of the battery cell is relatively high.
[0089] In some embodiments, the compaction density of the positive electrode film layer of the battery cell at 100% charge state is 2.00 g / cm 3 Up to 2.50g / cm 3 .
[0090] In some embodiments, the compaction density of the positive electrode film layer of the battery cell at 100% charge state is 2.00 g / cm 3 Up to 2.50g / cm 3 For example, the compaction density of the positive electrode film layer can be 2.00 g / cm 3 , 2.10g / cm 3 , 2.20g / cm 3 , 2.30g / cm 3 , 2.40g / cm 3 , 2.50g / cm 3 Or a range consisting of any two of the above values.
[0091] In the embodiments of the present application, in the implementation mode of the present application, the compaction density can be detected by equipment and methods known in the art, and the detection is carried out with reference to the standard GB / T 24533-2019. For example: after charging the battery cell to 100% charge state, the positive electrode plate is disassembled. Take the single-sided coated positive electrode plate (if it is a double-sided coated plate, the positive electrode coating on one side can be wiped first), punch it into small discs with an area of S, weigh it as M1, and measure the thickness as H1. Then wipe off the above-mentioned positive electrode film coating, leaving the substrate disc, weigh M0, and measure the thickness as H0. The coating weight of the positive electrode film layer is: (M1-M0) / S, and the thickness of the positive electrode film layer is: H1-H0. The compaction density of the positive electrode film layer is: coating weight of the positive electrode film layer / thickness of the positive electrode film layer.
[0092] By controlling the compaction density of the positive electrode film layer within the above range, the positive electrode material of the positive electrode film layer is stacked more densely, and the contact resistance between particles is small, which is conducive to the transmission of lithium ions, thereby improving the instantaneous discharge power of the battery cell at low temperature.
[0093] In some embodiments, the electrolyte includes a lithium salt, which may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate. The concentration of the lithium salt is 0.8 M to 1.2 M.
[0094] In some embodiments, the battery cell includes a separator disposed between a positive electrode and a negative electrode.
[0095] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0096] As an example, the main material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and ceramic. The separator can be a single-layer film or a multi-layer composite film, without special restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions. The separator can be a separate component located between the positive and negative electrodes, or it can be attached to the surface of the positive and negative electrodes. An inorganic particle coating, an organic particle coating, or an organic / inorganic composite coating can also be coated on the surface of the separator.
[0097] In some embodiments, the battery cell also includes a negative electrode current collector, which can be used to collect the negative electrode current of the battery cell, and can be a metal foil, a conductive polymer material, a carbon material or a composite current collector. For example, as a metal foil, a pure metal, an alloy, a surface-treated metal, including but not limited to stainless steel, copper, aluminum, nickel, nickel, titanium or silver, etc. can be used. The composite current collector may include a polymer material base layer and a metal layer. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).
[0098] In some embodiments, the negative electrode film layer is generally formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode film layer also includes a conductive agent and / or a binder. Exemplarily, the conductive agent can be at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The binder includes any one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA) or polymethyl methacrylate (PMMA) or a combination of at least two thereof.
[0099] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0100] A battery cell is a basic unit that can form a battery module or battery pack. It is an energy storage or release unit. Battery cells can be connected in series, in parallel, or in a mixed connection to form a battery module or battery pack. The shape of a battery cell can be cylindrical, square, or any other shape. For example, Figure 1 It is a battery cell 5 in a square structure.
[0101] The battery cell includes an outer package, which is used to encapsulate the electrode assembly and the non-aqueous electrolyte. The outer package of the battery cell can be a hard shell, such as an aluminum shell, a steel shell, etc. The outer package of the battery cell can also be a soft package, such as a bag-type soft package, etc.
[0102] In some embodiments, see Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0103] In a second aspect, the present application provides a battery device, which includes a plurality of battery cells according to any embodiment of the present application.
[0104] The battery device has at least the same advantages as any of the above-mentioned battery cells.
[0105] The battery device includes at least one of a battery module and a battery pack.
[0106] A battery module is assembled from battery cells. The battery module may contain one or more battery cells, and the specific number is selected by those skilled in the art according to the application and capacity of the battery module.
[0107] Figure 3 is a battery module 4 as an example. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0108] The battery pack may be assembled from battery modules. The battery pack may contain one or more battery modules, and the specific number is selected by those skilled in the art based on the application and capacity of the battery pack.
[0109] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0110] In a third aspect, the present application proposes an electrical device, which includes a battery device according to any embodiment of the second aspect of the present application.
[0111] The electric device has at least the same advantages as the battery device mentioned above.
[0112] An electrical device refers to a device or appliance that relies on electricity to achieve a specific function, and may be a household electrical device, an industrial electrical device, a commercial electrical device, a public facility electrical device, etc. Specifically, an electrical device may be a mobile phone, a laptop computer, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, an electric train, a ship and a satellite, an energy storage system, etc., but is not limited thereto. As an electrical device, a battery cell, a battery module or a battery pack may be selected according to its usage requirements.
[0113] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.
[0114] Example
[0115] The following examples describe the contents disclosed in the embodiments of the present application in more detail. These examples are for illustrative purposes only, as various modifications and variations within the scope of the contents disclosed in the embodiments of the present application are obvious to those skilled in the art. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0116] Example 1
[0117] 1. Preparation of negative electrode sheet
[0118] Artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and dispersant sodium carboxymethyl cellulose (CMC-Na) are mixed and dispersed in solvent deionized water at a mass ratio of 97:1:1:1, and stirred and mixed to prepare a negative electrode active slurry;
[0119] The negative electrode slurry is pressed into 0.164g / 1540.25mm 2 The amount of the coating is coated on both sides of the 6μm copper foil of the negative electrode current collector, and after drying, a negative electrode film layer is formed to obtain a negative electrode sheet.
[0120] 2. Preparation of positive electrode
[0121] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, and the positive electrode film layer includes a positive electrode conductive layer, a first film layer and a second film layer. The positive electrode current collector is an aluminum foil with a thickness of 13 μm.
[0122] 1) Positive electrode conductive paste
[0123] The positive electrode conductive layer is a positive electrode conductive slurry obtained by mixing and uniformly dispersing positive electrode conductive agent superconducting carbon and positive electrode binder polyvinylidene fluoride (PVDF) in a solvent N-methylpyrrolidone. The mass content of the positive electrode conductive agent in the positive electrode conductive slurry is 40%, and the mass content of the positive electrode binder is 60%.
[0124] 2) Preparation of the first positive electrode slurry
[0125] The first positive electrode slurry is prepared by mixing lithium iron phosphate material, conductive agent carbon nanotubes, binder polyvinylidene fluoride, and dispersant sodium carboxymethyl cellulose in a mass ratio of 97:1:1:1, adding N-methyl pyrrolidone, and mixing and stirring for 6 hours to obtain the first positive electrode slurry. The solid content of the first positive electrode slurry is 50wt%.
[0126] 3) Preparation of the second positive electrode slurry
[0127] The activated carbon (specific surface area 1372m 2 / g, particle size is 0.72μm), conductive agent carbon nanotubes, binder polyvinylidene fluoride, and dispersant sodium carboxymethyl cellulose are mixed in a mass ratio of 90:3:5:2, deionized water is added, and the mixture is stirred for 12h to obtain a positive electrode second slurry with a solid content of 15%wt.
[0128] The positive electrode conductive slurry, the first positive electrode slurry and the second positive electrode slurry are sequentially coated on both sides of the 13μm aluminum foil. After coating, drying, cold pressing, slitting and preparing the positive electrode sheet are performed. The film layer formed by the first positive electrode slurry is the first film layer, and the film layer formed by the second positive electrode slurry is the second film layer. The thickness of the first film layer is 86.7μm, and the thickness of the second film layer is 8μm.
[0129] The positive electrode material includes a carbon material located on at least a portion of the surface of the lithium iron phosphate material, wherein the carbon material is carbon black and has a carbon content of 1.30% based on the mass of the lithium iron phosphate material.
[0130] The volume average particle size Dv50 of the positive electrode material is 1.6 μm, and the gram capacity of the positive electrode material is 144 mAh / g. Based on the mass of the positive electrode material, the carbon content in the positive electrode material is 7.23%, the mass content of the activated carbon in the positive electrode material is 4%, the carbon content of the first film layer is 2.21%, and the carbon content of the second film layer is 4.02%.
[0131] 3. Isolation film
[0132] The isolation film comprises a base film, which is a 7 um polyethylene film layer with a porosity of 42%.
[0133] 4. Electrolyte
[0134] The electrolyte salt LiPF6 is mixed with a mixed solvent and an additive vinylene carbonate to prepare an electrolyte, wherein the concentration of the electrolyte salt in the mixed solvent is 1 mol / L, the mixed solvent includes vinyl carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 33:33:34, and the mass proportion of the added vinylene carbonate in the electrolyte is 2 wt%.
[0135] 5. Battery Cell
[0136] The positive electrode sheet, separator and negative electrode sheet were wound and wrapped with aluminum-plastic film bags, then injected with the configured electrolyte, vacuum packaged, and left to stand at room temperature for 6 hours to obtain a battery cell for subsequent testing. The compacted density of the positive electrode film layer of the battery cell at 100% charge state is 2.3g / cm 3 .
[0137] Comparative Examples 1-3
[0138] Comparative Examples 1-3 use a method similar to that of Example 1 to prepare battery cells. The difference from Example 1 is that no porous carbon material is added in Comparative Example 1, and the carbon content in the positive electrode material is different from that in Example 1; the difference between Comparative Examples 2 and Comparative Examples 3 and Example 1 is that the carbon content in the positive electrode material, the mass content of the added activated carbon, the carbon content of the second film layer, and the thickness of the second film layer are different. See Table 1 for specific values.
[0139] Example 2-3
[0140] Example 2-3 uses a similar method to Example 1 to prepare a battery cell. The difference between Example 2 and Example 1 is whether the activated carbon is subjected to a heat treatment at 1100°C; the difference between Example 3 and Example 1 is the composite method of the lithium iron phosphate material and the porous carbon material. In the positive electrode slurry of Example 3, the lithium iron phosphate material and the activated carbon are physically mixed, and the positive electrode film layer is not divided into a first film layer and a second film layer. See Table 2 for details.
[0141] Embodiment 4-7
[0142] Examples 4-7 use a similar method to Example 1 to prepare battery cells. The difference between Example 4-5 and Example 1 is the Dv50 of the activated carbon; the difference between Example 6-7 and Example 1 is the compaction density of the positive electrode film layer. See Table 3 for specific values.
[0143] Performance Testing
[0144] 1) Battery cell capacity test:
[0145] At -20℃, charge the battery cell at a constant current of 0.33C to a charge cut-off voltage of 3.8V, then charge at a constant voltage to a current of 0.05C, let stand for 30 minutes, and then discharge at a constant current of 0.33C to a discharge cut-off voltage of 2.0V, and record its actual discharge capacity as C0. The larger the discharge capacity of the battery cell, the greater the energy density.
[0146] 2) Storage capacity test of battery cells:
[0147] At 25°C, charge the battery cell at a constant current of 0.33C to 3.8V, and then charge at the cut-off voltage to a current of 0.05C. At this time, the battery cell is in a fully charged state, and the discharge capacity X0 is recorded. Store the fully charged battery cell in a 25°C environment, take it out every 30 days, and discharge it at a constant current of 0.1C to the lower cut-off voltage. The discharge capacity after storage for a period of time is obtained and recorded as X1; the capacity retention rate is X1 / X0.
[0148] 3) DC resistance DCR test of battery cells:
[0149] Refer to the method in GB / T 31467 "Performance test specification for high-power lithium-ion power batteries for HEV".
[0150] ① At room temperature, charge the battery cell to 3.8V at a constant current of 0.33C, let it stand for 1 minute, then charge it at a constant voltage of 3.8V until the current decays to 0.02C, let it stand for 30 minutes, and discharge it to 2.0V at a constant current of 0.33C. Record the discharge capacity A0 at this time, in Ah.
[0151] ② Charge 10% A0 Ah at a constant current of 0.33C and adjust the battery cell to 10% SOC.
[0152] ③ After placing the battery cell at -20℃ for 2h, discharge it at a constant current of 4C for 5s, record the discharge ΔU and discharge I, and calculate the discharge DCR data of the lithium-ion battery by the following formula: DCR discharge = discharge ΔU / discharge I. Among them, ΔU discharge represents the voltage change within 5s from the start of discharge, and I discharge represents the current value within 5s from the start of discharge.
[0153] Results Analysis
[0154] Table 1
[0155]
[0156] Compared with Example 1, no activated carbon was added to the positive electrode material in Comparative Example 1, and the DCR of the battery cell of Example 1 was significantly lower than that of Comparative Example 1, indicating that the addition of activated carbon significantly improved the instantaneous discharge power of the battery cell of Example 1.
[0157] Compared with Example 1, in Comparative Example 2, relatively more activated carbon is added to the positive electrode material, and the carbon content of the positive electrode material also increases; compared with Example 1, relatively less activated carbon is added to the positive electrode material in Comparative Example 3, and the carbon content of the positive electrode material also decreases; compared with the results of Comparative Example 2, the DCR of Example 1 is smaller and the capacity is greatly reduced. From the experimental results, it can be seen that although adding more activated carbon reduces the DCR of the battery cell and improves the instantaneous power of the battery cell, it affects the energy density of the battery cell, resulting in a smaller capacity of the battery cell; compared with the results of Comparative Example 3, the DCR of Example 1 is smaller. From the experimental results, it can be seen that adding a smaller mass content of activated carbon does not significantly improve the instantaneous power performance of the battery cell.
[0158] Table 2
[0159]
[0160] Compared with Example 1, the activated carbon in Example 2 was not heat-treated, resulting in a relatively large DCR of the battery cell in Example 2. The experimental results show that the activated carbon in the battery cell in Example 1 was heat-treated to remove oxygen-containing functional groups, reduce impedance, and thus improve the instantaneous discharge power of the battery cell.
[0161] Compared with Example 1, the composite method of activated carbon and lithium iron phosphate material in Example 3 is different. The activated carbon and lithium iron phosphate material in Example 3 are physically mixed, while in Example 1, the second film layer containing activated carbon is located on at least part of the surface of the first film layer containing lithium iron phosphate material, so that the DCR of the battery cell in Example 1 is relatively small. The experimental results show that the composite method of activated carbon and lithium iron phosphate material in Example 1 can shorten the migration path of lithium ions, thereby improving the instantaneous discharge power of the battery cell.
[0162] Table 3
[0163]
[0164] Compared with Example 1, the activated carbon Dv50 of Example 4 and Example 5 is different, and the battery monomer DCR of Example 4 and Example 5 is significantly greater than that of Example 1. From the experimental results, it can be seen that too large or too small Dv50 of activated carbon will affect the DCR of the battery monomer, and being within a suitable range is conducive to reducing the DCR of the battery monomer, thereby increasing the instantaneous discharge power of the battery monomer.
[0165] Compared with Example 1, the compaction density of the positive electrode film layer of Example 6 and Example 7 is different. The compaction density of the positive electrode film layer of Example 7 is significantly lower than that of Example 1, and the DCR data of Example 7 is significantly higher than that of Example 1. It can be seen from the experimental results that the compaction density of the positive electrode film layer will affect the instantaneous discharge power of the battery cell. Therefore, controlling the compaction density of the positive electrode film layer of the battery cell within an appropriate range is beneficial to reducing the DCR of the battery cell and improving the instantaneous discharge power of the battery cell.
[0166] The capacity retention rate data results of Examples 1-7 and Comparative Examples 1-3 indicate that adding activated carbon does not affect the storage life of the battery cells.
[0167] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in some manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A battery cell, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein: The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, the positive electrode film layer includes a positive electrode material, the positive electrode material includes a lithium iron phosphate material and a porous carbon material, and at least part of the surface of the lithium iron phosphate material includes a carbon material; based on the total mass of the positive electrode material, the carbon content of the positive electrode material is 3% to 10%.
2. The battery cell according to claim 1, characterized in that: The positive electrode film layer includes a first film layer and a second film layer, wherein: The first film layer is disposed on at least one surface of the positive electrode current collector, and the first film layer includes the lithium iron phosphate material; The second film layer is arranged on a surface of the first film layer away from the positive electrode current collector, and the second film layer includes the porous carbon material.
3. The battery cell according to claim 2, characterized in that: The thickness of the first film layer is 50 μm to 100 μm; and / or, The second film layer has a thickness of 4 μm to 14 μm.
4. The battery cell according to any one of claims 2 to 3, characterized in that: Based on the total mass of the positive electrode material, The carbon content of the first film layer is 1.5% to 3%; and / or, The carbon content of the second film layer is 2% to 7%.
5. The battery cell according to any one of claims 1 to 4, characterized in that: The mass content of the porous carbon material is 2.0% to 7.0% based on the total mass of the positive electrode material.
6. The battery cell according to any one of claims 1 to 5, characterized in that: The porous carbon material includes at least one of activated carbon, carbon molecular sieve, activated carbon fiber and mesoporous carbon. 7 . The battery cell according to claim 1 , wherein the volume average particle size Dv50 of the porous carbon material is 0.50 μm to 10 μm.
8. The battery cell according to any one of claims 1 to 7, characterized in that: The specific surface area of the porous carbon material is 1000 m 2 / g to 2000m 2 / g.
9. The battery cell according to claims 1-8, characterized in that: The porous carbon material is used as a positive electrode material after being heat-treated at 900 to 1100° C., so that the oxygen-containing groups on the surface of the porous carbon material are reduced.
10. The battery cell according to any one of claims 1 to 9, characterized in that: Based on the total mass of the lithium iron phosphate material, the carbon content of the lithium iron phosphate material is 1% to 2%.
11. The battery cell according to any one of claims 2 to 10, wherein: The lithium iron phosphate material includes lithium iron phosphate and modified compounds thereof. 12 . The battery cell according to claim 1 , wherein the positive electrode material comprises a conductive agent, wherein the conductive agent comprises at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. 13 . The battery cell according to claim 12 , wherein the carbon content of the conductive agent is 0.2% to 1% based on the total mass of the positive electrode material.
14. The battery cell according to any one of claims 1 to 13, characterized in that: The gram capacity of the positive electrode material is 130 mAh / g to 170 mAh / g.
15. The battery cell according to any one of claims 1, characterized in that: The battery cell is in a 100% charged state, and the compaction density of the positive electrode film layer is 2.00 g / cm 3 Up to 2.50g / cm 3 .
16. A battery device comprising the battery cell according to any one of claims 1 to 15.
17. An electrical device comprising the battery device according to claim 16.
Citation Information
Patent Citations
Positive electrode for lithium ion capacitor and lithium ion capacitor using the positive electrode, and production methods thereof
CN110828189A
Positive pole piece and preparation method thereof, secondary battery and electronic device
CN116111045A
Lithium ion secondary battery
JP2007207535A
Lithium secondary battery, positive electrode therefor, and its manufacturing method
JP2008034215A
Nonaqueous secondary battery
JP2017059297A